Information Sphere Challenges in the Processes of Formulation of Armenian Civil Identity - Nazaryan, Hayk; Mkrtchyan, Arem; Tumanyan, Gagik (Journal of Sociology: Bulletin of Yerevan University, 2021)
Nowadays, the significant impact of informational communications creates certain risks to social life. In this context, information is often used as a mean of manipulation and distortion of facts, as well as an instrument of aggression. Therefore, regulation of informational challenges, first of all, plays an important role on the side of security (especially for the vulnerable segments of population). In modern societies, civic identity formation with its basic elements can provide relevant mechanisms of regulation, correction, and complementation of informational policies towards mentioned problems. In particular, civic identity in its scientific interpretations presupposes such manifestations as civic participation (directed to the needs of the community), civic knowledge (in particular, competence regarding democratic institutions and principles), social trust (which serves as a base for personal self-identification with other citizens and political institutions). The effective formation of the mentioned elements of civic identity, functioning with the mechanisms of civic education and in the context of the growing role of information, contributes a more conscious and competent attitude towards information resources. On the other hand, citizens' awareness broadens the field of social visibility, hence the opportunities and practices that can contribute to more effective self-organization of local communities. Thus, in this article, the peculiarities of civil identity formation, in the case of border Armenian rural communities, were analyzed in the context of actual informational challenges.
Keywords: informational challenges; border rural communities; civil identity; civic participation; civic knowledge